Uma contribuição para o ensino-aprendizagem da disciplina Auditoria contábil - Vilela, Marcus Sérgio Satto (2008)
The central theme of this study is the search for methods and techniques to support the teaching-learning process at the higher education, more specifically in the Accounting Audit discipline. According to the educational focus and how to learn each student, are presented different obstacles in relation to teaching-learning. In this dimension, the goal of this study was to identify and to propose strategies to minimize the difficulties of teachers of the discipline Accounting Audit for greater efficiency in the teaching-learning process, especially in the professional experience. Therefore, it was necessary to present an educational theoretical reference, which are reviewed and discussed the variables in the teaching-learning process, and an evaluation of the strategies for teaching commonly used in higher education. The documentary evaluation of the Accounting Audit discipline in the history of the Accounting course, and the adherence to its programmatic content to the national and global professional requirements, allowed an adequate characterization of the curriculum structure. The achievement of the research with teachers of this discipline in Minas Gerais, corroborates with the studied theories, also supported by the results of other studies. It is observed that the lack of pedagogical training in teachers and technological and structural limitation of the universities creates a gap between the teaching academic and the professional technical formation. The change of attitude of the teacher, as regards the limitations and difficulties in the teaching-learning process, can and must be supported by the use of alternative strategies for teaching, so that, it allows to present for the student, the appropriate professional life experience in the activity of the accounting Audit